The beach [a novel] - Garland, Alex 1970- (Riverhead Books, 1997)
A young backpacker in Thailand searching for something different learns of the existence of an idyllic island which is not even on the map. The novel describes his jungle journey to reach the island where he discovers a secret commune of international drifters living off fish and pot. The man's arrival coincides with growing tension between factions, leading to the commune's violent demise. A first novel.
Keywords: Beaches -- Southeast Asia -- Fiction; Südostasien; Southeast Asia -- Fiction; Fiktionale Darstellung; Adventure fiction